Novel Fuzzy Assignment Problem Using Hexagonal Fuzzy Numbers. Issue 1 (March 2021) - Thiruppathi, A.; Kirubhashankar, C. K.
Abstract: In this paper, a hexagonal fuzzy assignment problem employing a fuzzy new ranking technique is applied. This method requires less number of iterations to succeed in an optimality solution compared to the prevailing methods. Numerical examples show the effectiveness of the proposed fuzzy hexagonal assignment problem.